Intravenous dexmedetomidine as an adjunct to subarachnoid block: A simple effective method of better perioperative efficacy - Rekha Kumari; Anil Kumar; Sushil Kumar; Rakesh Singh (Wolters Kluwer Medknow Publications, 2017)
Background and Aim: Dexmedetomidine (D) is a α2 agonist, has anesthetic and analgesic-sparing property. The objective of this study was to evaluate the effect of intravenous (I.V.) dexmedetomidine on the duration of sensory and motor block, postoperative analgesia, the level of sedation and side effect. Material and Methods: Sixty patients were randomly divided into two groups of thirty each. Group D received dexmedetomidine infusion @1 mcg/kg over 10 min and then @ 0.6 mcg/kg/h for rest of duration during surgery, Group C (control) received a similar volume of normal saline infusion before spinal anesthesia with 3 ml of bupivacaine 0.5%. Time of onset and regression time for sensory and motor blockade, the maximum upper level of sensory blockade, duration of postoperative analgesia, Ramsay sedation score and hemodynamic parameters were recorded. Intraoperative bradycardia and atropine requirement along with other side effect were also recorded. Results: The duration of sensorimotor block was significantly longer in D Group (341.7 ± 20.8 min for sensory block and 278.0 ± 11.0 min for motor block) as compared to control group (329.5 ± 22.1 min for sensory block and 250.0 ± 14.8 min for motor block), which was statistically significant (P < 0.05). The mean time for two dermatomal regression of sensory blockade was significantly prolonged in dexmedetomidine group (115.5 ± 8.7 min) compared to control group (95.8 ± 11.4) (P < 0.001). Intraoperative Ramsay sedation scores were significantly higher in D Group (mean - 3.4 ± 0.7, range - 2-4) as compared to C Group (mean - 2.9 ± 0.3, range - 2-4) (P < 0.001). 26.7% (8/30) cases had bradycardia that required atropine as compared to control group (2/30), and none of the patients in the dexmedetomidine group had postoperative shivering as compared to 10% in control group (P = 0.056). Statistical analysis was performed with statistical package for the social science version-20 using analysis of variance/Chi-square test/unpaired t-test, and P < 0.05 was considered statistically significant. Conclusion: I.V. dexmedetomidine significantly prolongs the duration of sensory and motor block of bupivacaine spinal anesthesia. Dexmedetomidine provides an excellent sedation during surgery.